Governance of the extended enterprise : bridging business and IT strategies (John Wiley & Sons, 2005)
Globalization and worldwide communications have overridden national boundaries. In many markets, the effect of global financial interdependence (governmental, political, and business) is now so interconnected that they must be considered with almost any decision being made.